The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1002/jcb.26833
|View full text |Cite
|
Sign up to set email alerts
|

Bone mesenchymal stem cells pretreated with erythropoietin enhance the effect to ameliorate cyclosporine A‐induced nephrotoxicity in rats

Abstract: An increasing number of experiments and clinical trials have demonstrated the safety, feasibility, and efficacy of mesenchymal stem cells (MSCs)-based therapies for the treatment of various diseases. The main drawbacks of MSC therapy are the lack of specific homing after systemic infusion and early death of injected cells because of the injury micro-environment. We pretreated bone mesenchymal stem cells (BMSCs) with erythropoietin (EPO) to investigate their positive effect on cyclosporine A (CsA)-induced nephr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 45 publications
0
24
0
Order By: Relevance
“…We observed that CXCR4 which was a pivotal mediator of migration and engraftment of MSCs was upregulated following EPO treatment. These changes enhanced the migration ability of BMSCs [18].…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…We observed that CXCR4 which was a pivotal mediator of migration and engraftment of MSCs was upregulated following EPO treatment. These changes enhanced the migration ability of BMSCs [18].…”
Section: Discussionmentioning
confidence: 94%
“…These BMSCs significantly inhibited the apoptosis of HK2 cells from the toxicity of cyclosporin A (CsA). Moreover, the one-time infusion treatment with EPO-BMSCs significantly improved the renal function of CsA-induced chronic toxic renal injury, and promoted the repair of renal fibrosis in rats [18].…”
mentioning
confidence: 90%
“…After incubation with EPO, most of the cells exhibited parallelly-oriented laments organized along the cell axis. We observed that C-X-C chemokine receptor type 4 (CXCR4), a pivotal mediator of migration and engraftment in MSCs, was up-regulated following EPO treatment, enhancing the migration ability of BMSCs [20].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the single infusion treatment with EPO-BMSCs signi cantly improved the renal function in CsAinduced chronic toxic renal injury, and promoted the repair of renal brosis in rats [20].…”
Section: Introductionmentioning
confidence: 94%
“…These BMSCs signi cantly inhibited the apoptosis induced by cyclosporine A (CsA) toxicity in HK2 cells. Moreover, the single infusion treatment with EPO-BMSCs signi cantly improved the renal function in CsA-induced chronic toxic renal injury, and promoted the repair of renal brosis in rats [18].…”
Section: Introductionmentioning
confidence: 95%